Single Stage Cranioplasty with Customized Polyetheretherketone Implant After Removal of Eosinophilic Granuloma skull bone: Case Report (Bangladesh Journal of Neurosurgery, 2024)
Eosinophilic granuloma is a localized form of Langerhans cell histiocytosis, most commonly involving the skeletal system. Their origin from the dura is rare with only a handful of cases on record. We present one such rare case of an eosinophilic granuloma originating from the Extradural with secondary osseous invasion in a 20 year old male who presented with a swelling in the right fronto orbital region. A complete resection was scheduled with single stage reconstruction of the frontoorbital bone by a polyetheretherketone (PEEK) specific implant. This implant was computer-assisted designed and manufactured and verified by the surgeon before the intervention.Bang. J Neurosurgery 2024; 13(2): 152-156